Ultrasonographic Diagnosis of Urinary System Affections in Dogs - Barot, Hiren Mukeshbhai; Patel, Malhar Dineshbhai; Parikh, Pineshkumar Vasantlal (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
In present investigation total 37 dogs with different urinary system affection were included. Common physical findings in urinary tract  disease were stranguria / dysuria, haematuria, anuria and urinary incontinence. Ultrasonographic examinations showed hyperechoic  calculi with acoustic shadow in case of kidney stone; lack of demarcation between the cortex and medulla and enlarged kidney in  hydronephrosis, and non-homogenous small kidneys with loss of corticomedullary differentiation when dog was affected with chronic  kidney disease. Cystic and urethral calculi ultrasonographically appeared as hyperechoic structures creating acoustic shadowing.  Further renal mass, cystitis and urinary bladder mass were clearly diagnosed using ultrasonography. On the basis of present findings,  we concluded that ultrasonography could be best exploited in the diagnosis of urinary system affections.
Keywords: Bladder mass; Cystic calculi; Cystitis; Dog; Hydronephrosis; Kidney stone; Renal mass; Ultrasonography